Susceptibility of Neisseria meningitidis and Neisseria gonorrhoeae isolates to N-formimidoyl thienamycin. - Dudek, E J (1982)
A diverse collection of 123 meningococcal and 126 gonococcal isolates was tested for susceptibility to N-formimidoyl thienamycin (N-F-thienamycin; MK0787) and to penicillin G (PEN). All of the meningococci were susceptible to both of these, as well as to rifampin. Among gonococci, beta-lactamase-producing strains, which were resistant to PEN, were susceptible to N-F-thienamycin. Among non-beta-lactamase-producing strains, the minimal inhibitory concentrations of N-F-thienamycin and PEN were less than or equal to 1.28 micrograms/ml. Of these, the strains with PEN minimal inhibitory concentrations toward the higher end of the range were likely to be more susceptible to N-F-thienamycin, whereas the strains that were highly susceptible to PEN were likely to have higher minimal inhibitory concentrations of N-F-thienamycin.